The Adoption of E-Learning in Teaching and Learning Processes; an Option for Life-Long Education - Baginda Simaibang (International Conference on Education and Language (ICEL), 2013)
The objective of this study is to investigate the benefits of the adoption of electronic learning (E-Learning)in teaching and learning processes. E-Learning is an educational approach that utilizes computer technology, particularly digital technologies that are internet-based, to provide instruction and learning experiences. The definition of e-learning refers to a wide range of applications and processes designed to deliver instruction through electronic means. This means is normally employed over the network. It includes video streamings, video-conferencing through satellite transmission, online learning, web-based training (WBT), computer-based training(CBT), internet, intranet, PCs at work, school or home, interactive multimedia, games, simulations, flash animation, online tutorials, video and audio resources such as tapes, CD, and DVD. Research indicates that e-learning signals the paradigm shift in education and training that is in progress. It provides a new set of tools and instructional practices that overcome distance barriers, logistic costs and adds value to existing traditional learning process, such as classroom lectures, textbooks, video and CD-ROM. As computer technology is introduced, it immediately becomes integrated with the instructional technology that preceded it. This is called "blended learning" or "hybrid learning" delivery. Old and new instructional methods are blended, and more technically we are blending a sequence of both asynchronous (self-paced) and synchronous (collaborative) learning events. The revolutionary impact of e-learning lies not simply in having a multimedia platform on a single desktop, but also it is the combined power of a world-wide network of computers that connects authors, instructors and learners globally with the immediacy of text, graphics, audio and video, as well as interactivity and collaborative interactions. The tremendous education and learning benefits that e-learning has offered covers an increase of productivity, reduction of training cost, competitive advantage, education transformation, train anywhere and any time globally 24/7, elimination of knowledge gap, extended education chains, re-skill learners and instructors, self-paced learning and promotion of teaching and learning innovations. The internet-based education represents the underlying principle that makes lifelong learning a reachable and accessible learning for all learners.